PEMILIHAN KRIM WAJAH TERBAIK YANG MENGANDUNG CERAMIDE MENGGUNAKAN METODE TOPSIS - Rifa Nurafifah Syabaniah; Andi Riyanto; Eva Marsusanti; Susilawati Susilawati (LPPM STMIK STIKOM Indonesia, 2020)
Dryness of the skin on the face makes it uncomfortable, one treatment to avoid dryness of the facial skin is to use facial creams that contain ceramide. the process of selecting the best face cream that contains ceramide takes a long and difficult time. This process requires precision and proper judgment. In this study the TOPSIS method is used to solve the problem, so that the process of selecting facial creams can be done quickly and precisely. the test results using the TOPSIS method, the results obtained that the selection of face cream that contains the best ceramide based on three price criteria, packaging and composition is the P1 brand code with a preference value (vi) of 0.725 is ranked 1st for the assessment of each criterion K1 = 21.07, K2 = 8.62 and K3 = 9.71. This means that the P1 brand code has the highest value of other face cream products with the lowest price rating of other products namely rating 5 (21.07), the packaging is quite good with a rating of 3 (8.62) and the composition is quite a lot with a value of 3 (9, 71).